2007
DOI: 10.1063/1.2711188
|View full text |Cite
|
Sign up to set email alerts
|

Restricted open-shell Kohn-Sham theory: Simulation of the pyrrole photodissociation

Abstract: The authors study the photodissociation reactions of pyrrole and N-methylpyrrole using first-principles molecular dynamics. The first excited state is described with restricted open-shell Kohn-Sham theory. They find a small barrier in the excited state potential energy surface. The possibility of energy redistribution near the Franck-Condon region leads to two different reaction channels in on-the-fly simulations on a single diabatic potential energy surface. The results are discussed in comparison with previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 38 publications
(32 reference statements)
2
39
1
Order By: Relevance
“…[14] Although for the slow component the agreement between our experiment and the calculations of Frank et al [14] is very good, there is a discrepancy for the fast component.…”
contrasting
confidence: 38%
See 3 more Smart Citations
“…[14] Although for the slow component the agreement between our experiment and the calculations of Frank et al [14] is very good, there is a discrepancy for the fast component.…”
contrasting
confidence: 38%
“…We believe that the dissociation of Py in this red wing of the absorption spectrum takes place entirely on the S 1 ( 1 ps*, 1 1 A 2 ) excited electronic state, as was proposed by Frank et al [14] The fast H component appears due to rapid dissociation (< 0.1 ps) on this electronic state caused by the interaction of the antibonding s* orbital localized on the NÀH bond. The slow H component appears due to excited-state dissociation following the relaxation in the local minimum near the FranckCondon region.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…1b). The NH-stretching mechanism, which has been explored by quantum [19][20][21] and trajectory-based [22,23] dynamics simulations, should be the main source of fast H atoms. Time-resolved femtoseconds investigations [24] have revealed that when pyrrole is pumped at 250 nm, this process takes place in approximately 0.1 ps, which has been also confirmed by dynamics simulations [23].…”
Section: Introductionmentioning
confidence: 99%